METHODS OF INTRODUCING ENGLISH WORD STRUCTURE TO UZBEK STUDENTS - Mukadas Ikromovna Murodova (Science and Education, 2020)
The article deals with the methods of introducing English word structure. The advantages of these methods are discussed in this article. We should use different types of methods during teaching classes. And we can use majority of modern techniques while teaching simple sentence. With international materials it is obvious that the needs of individual students and teachers, as well as the expectations of particular schools in particular countries, can never be fully met by the materials themselves while studying Simple Sentence.